Nutrient Availability and Changes on Chemical Attributes of a Paleudult Soil Amended with Liquid Sewage Sludge and Cropped with Surinam Grass - Luiz Carlos Ceolato; Ronaldo Severiano Berton; Aline Renée Coscione (Applied and Environmental Soil Science)
The liquid sewage sludge (LSS) was applied on a field experiment during four years at successive applications to evaluate the changes in soil attributes and on Surinam grass (Brachiaria decumbens) uptake of nutrients. A randomized blocks experimental design, with two treatments (with and without LSS) and three repetitions, was used. Land application of LSS did not alter soil organic matter and exchangeable K until 40 cm depth. However, it increased soil pH, base saturation, labile P, and available Zn and did not change the concentrations of available B (hot water) and Cu, Fe, and Mn (DTPA) at 0–20 cm and 20–40 cm depths and LSS was a source of N, K, P, Ca, Mg, and Zn for the grass, but decreased leaf Mn concentration.